Gemini pyridinium amphiphiles for the synthesis and stabilization of gold nanoparticles for drug delivery - Alea-Reyes, Maria E.; Gonzalez, Asensio; Calpena, Ana C.; Ramos-López, David; Lapuente, Joaquín de; Pérez-García, Lluïsa (Elsevier, 2017)
Hypothesis